Relationship between leg stiffness and kinematic variables according to the load while running - Hyun, S. H.; Ryew, C. C. (Korean Journal of Sport Biomechanics, 2017)
Objective: This study aimed to investigate the relationship between leg stiffness and kinematic variables according to load while running. Method: Participants included eight healthy men (mean age, 22.75 ± 1.16 years; mean height: 1.73 ± 0.01 m; mean body weight, 71.37 ± 5.50 kg) who ran with no load or a backpack loaded with 14.08% or 28.17% of their body weight. The analyzed variables included leg stiffness, ground contact time, center of gravity (COG) displacement and Y-axis velocity, lower-extremity joint angle (hip, knee, ankle), peak vertical force (PVF), and change in stance phase leg length. Results: Dimensionless leg stiffness increased significantly with increasing load during running, which was the result of increased PVF and contact time due to decreased leg lengths and COG displacement and velocity. Leg length and leg stiffness showed a negative correlation (r = -.902, R2 = 0.814). COG velocity showed a similar correlation with COG displacement (r = .408, R2 = .166) and contact time (r = -.455, R2 = .207). Conclusion: Dimensionless leg stiffness increased during running with a load. In this investigation, leg stiffness due to load increased was most closely related to the PVF, knee joint angle, and change in stance phase leg length. However, leg stiffness was unaffected by change in contact time, COG velocity, and COG displacement.